Positive association of breastfeeding on respiratory syncytial virus infection in hospitalized infants: a multicenter retrospective study - Min Jeong Jang; Yong Joo Kim; Shinhye Hong; Jaeyoon Na; Jong Hee Hwang; Son Moon Shin; Young Min Ahn (The Korean Pediatric Society, 2020)
Background Breastfeeding reportedly reduces the overall frequency of infections. Respiratory syncytial virus (RSV), the most common respiratory pathogen in infants, involves recurrent wheezing and has a pathogenic mechanism related to airway structural damage. Purpose This study aimed to investigate whether breastfeeding has a beneficial effect against RSV-induced respiratory infection compared to formula feeding among infants in Korea. Methods We retrospectively reviewed the medical records of infants under 1 year of age who were admitted with RSV infection between January 2016 and February 2018 at the department of pediatrics of 4 hospitals. We investigated the differences in clinical parameters such as cyanosis, chest retraction, combined infection, fever duration, oxygen use, oxygen therapy duration, intensive care unit (ICU) admission, and corticosteroid treatment of exclusive breast milk feeding (BMF), artificial milk formula fed (AMF), and mixed feeding (MF) groups. Results Among the 411 infants included in our study, 94, 161, and 156 were included in the BMF, MF, and AMF groups, respectively. The rates of oxygen therapy were significantly different among the BMF (4.3%), MF (8.1%), and AMF (13.5 %) groups (P=0.042). The odds ratios (ORs) for oxygen therapy was significantly higher in the AMF group than in the BMF group (adjusted OR, 3.807; 95% confidence interval, 1.22-11.90; P=0.021). The ICU admission rate of the BMF group (1.1%) was lower than that of the MF (3.5%) and AMF (4.5%) groups; however, the dissimilarity was not statistically significant (P=0.338). Conclusion The severity of RSV infection requiring oxygen therapy was lower in the BMF than the AMF group. This protective role of human milk on RSV infection might decrease the need for oxygen therapy suggesting less airway damage.